Between Oxus and Jumna - Toynbee, Arnold, 1889-1975 (London Oxford University Press, 1961)
Noted historian's account of his recent travels through the portions of India, Pakistan and Afghanistan, lying between the Oxus and Jumna Rivers.
Include Maps, Illustration and Index
Keywords: Travel -- Afghanistan -- Pakistan